2001
DOI: 10.1645/0022-3395(2001)087[0907:miianc]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Monogeneans in Introduced and Native Cichlids in México: Evidence for Transfer

Abstract: We examined 2 cichlid fish species native to México, Cichlasoma callolepis and C. fenestratum, and 2 introduced African cichlids, Oreochromis aureus and O. niloticus, from 3 localities in southeastern México for monogeneans. Six monogenean species infected the African cichlids: Cichlidogyrus haplochromii, C. dossoui, C. longicornis longicornis, C. sclerosus, C. tilapiae, and Enterogyrus malmbergi. We found all these parasite species, except C. haplochromii and C. dossoui, on the native C. fenestratum and C. ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 3 publications
3
46
0
3
Order By: Relevance
“…These possible consequences need to be explored. At one level we found that, despite the transfer of native parasites to the introduced host (see also Jiménez-García et al, 2001), the native V. maculicauda harboured more than twice the number of parasite species compared with the introduced O. niloticus, both in the overall sampled population and at the scale of individual hosts. Thus, the introduced host still experienced a net benefit in terms of lower parasite species richness compared with the native host.…”
Section: Discussionmentioning
confidence: 86%
“…These possible consequences need to be explored. At one level we found that, despite the transfer of native parasites to the introduced host (see also Jiménez-García et al, 2001), the native V. maculicauda harboured more than twice the number of parasite species compared with the introduced O. niloticus, both in the overall sampled population and at the scale of individual hosts. Thus, the introduced host still experienced a net benefit in terms of lower parasite species richness compared with the native host.…”
Section: Discussionmentioning
confidence: 86%
“…Monogenoideans are parasites with direct life cycle and resistant to elimination when translocated (PÉREZ-PONCE DE LEÓN et al, 2000). Thus, species of the genus Cichlidogyrus translocated with O. niloticus colonized species of endemic cichlids of Mexico (JIMÉNEZ-GARCÍA et al, 2001) and Panama (ROCHE et al, 2010), due to its relative parasite specificity. In contrast, C. tilapiae, the only species of helminth parasitizing this invasive fish in the region of this study, was not competent to invade any of the 16 species of native cichlids, fish ecologically similar.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the results of this fish introduction in Brazilian fish farms do not reflect what occurs in the natural environment; it indicates loss of monogenoideans species with the translocation of this tilapia from other regions of Brazil to the studied area. Therefore, the acquisition and transmission of exotic parasites depend on a complex set of factors, including biological aspects of host and parasite, host-parasite interaction and scalespace (JIMÉNEZ-GARCÍA et al, 2001;ROCHE et al, 2010;GENDRON et al, 2012;PATERSON et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fuera de su lugar de origen, es señalada como especie introducida y como toda especie, tiene sus propios helmintos parásitos y en los diferentes sitios de cultivo, han registrado la presencia de estos, tanto en condiciones de encierro como en vida libre (Jiménez-García et al, 2001; Zonolo et al, …”
Section: Introductionunclassified